The COVID-19 Pandemic, Stress, and Eating Practices in the United States - Jagdish Khubchandani; Jayanthi Kandiah; Diana Saiki (MDPI AG, 2020)
The COVID-19 pandemic has disrupted the lives of people worldwide. In this study, we assessed the burden of stress during the pandemic and its relationship with eating practices in a national random sample of American adults. Data were collected using an online survey and the participants were asked about their demographic characteristics, perceived stress, and eating practices in April 2020. Compared to their counterparts, average stress scores were statistically significantly higher for racial and ethnic minority individuals, those who were employed part-time, were single, lived in the Midwest, and were ≤35 years of age. More than one-tenth of the participants reported practicing more unhealthy eating practices during the pandemic lockdowns: fasting (16%), restricting eating (20%), skipping meals (25%), and overeating (39%). Concerning the overall perception of diet, nearly a third reported that their diet had worsened during the pandemic (31%). In adjusted and unadjusted analyses after controlling for demographic characteristics, stress scores were statistically significantly higher for those engaging in unhealthy eating practices and those who reported that their diet had worsened. Policymakers and public health practitioners should redouble their efforts in preventing morbidity and premature mortality by implementing interventions that address the multiple detrimental stressors of the COVID-19 pandemic.